Existence of Asymptotically Almost Periodic Solutions for Damped Wave Equations - Lizama-Yanez, C (2011)
In this paper, a class of nonlinear damped wave equations of the form ?u (t)+u (t)=?Au(t)+?Au (t)+f(t,u(t)), t?0, satisfying ??